Collisions of HGVs with bridges - McGuinn, P. (Institution of Civil Engineers, 1996)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Paper presented at 'Safety of bridges', ICE/Highways Agency symposium held on 4-5 July 1996.